The planets - Couper, Heather; Dinwiddie, Robert; Farndon, John; Henbest, Nigel; Hughes, David W. (David Wolstenholme), 1941-; Sparrow, Giles, 1970-; Stott, Carole; Stuart, Colin (Science writer); DK Publishing, Inc.; Smithsonian Institution (London ; New York : Dorling Kindersley, 2014)
Featuring all-new 3D models built using data gathered by NASA and the European Space Agency.--
Family of the sun -- Our star -- Rocky worlds -- Gas giants -- Outer limits.
At head of title: DK Smithsonian.
Includes bibliographical references and index.
Subtitle from cover.
Keywords: Solar system